Companion Animal Economics : The Economic Impact of Companion Animals in the UK : Research Report /: The Economic Impact of Companion Animals in the UK : Research Report. ([2016]) - Hall, Sophie (Sophie Susannah); Dolling, Luke; Bristow, Katie; (Professor of entrepreneurship and strategic foresight), Fuller, Ted; Mills, D. S
No abstract available